Making it Concrete: Analysing the Role of Concrete Plants’ Locations for Circular City Policy Goals - Van den Berghe, Karel B.J.; Verhagen, Teun J. (Frontiers in Built Environment, 2021)
Increasingly, space for remanufacturing is seen as the most valuable resource to achieve circular economy (CE) policy goals, in particular for cities. However, in many cities, industrial urban areas are increasingly subject of – mostly circular designed - residential redevelopment. The proposition of this paper is that these diminishing industrial areas host, at least potentially, essential functions necessary to ‘close the material loop’. The reason why policy makers neglect the necessity of remanufacturing capacity, is because it is difficult to pinpoint the ‘ideal’ geography of a circular loop. Most (circular) products can be transported limitless, thus their remanufacturing functions can be located around the world. But what if a critical material cannot be transported limitless and has circular potential? Therefore, this paper focuses on concrete for two reasons. First, concrete is by far the most abundant material in urban areas. Second, newly/circular made fluid concrete can only be transported for a limited time and distance. The hypothesis of this paper is that concrete plants are and will become essential for circular cities. Subsequently, we focus on the Dutch city of The Hague and combine a Material Flow Analysis with the locations of the concrete resupply chain. Our results show that potentially The Hague has a 100% circular concrete chain, but the importance of its concrete plant is (implicitly) neglected. We conclude that The Hague is illustrative for the problem of many circular cities that are without (implicitly) taking into account the whole circular resupply chain, jeopardized today a future urban CE.